Respostas

2014-07-29T23:23:23-03:00
A) x² + 5x + 4= 0            A= 1  B= 5  C= 4

Δ= b² - 4 * a * c
Δ= ( 5 )² - 4 * 1 * 4  
Δ= 25 - 16 
Δ= 9 
  
x = -b ± √Δ
        2 * a 
x = -5 ± √9
        2 * 1 
x = -5 ± 3             x' = -5 + 3 = -2 = 1 
         2                           2        2  
        
                           x" = -5 - 3 = -8 = -4 
                                      2       2    


b) 7x² + x + 2 = 0         a = 7    b = 1     c = 2

Δ= b² - 4 * a * c
Δ= ( 1 )² - 4 * 7 * 2 
Δ= 1 - 56
Δ= - 55

x = -b ± √Δ
        2 * a 
x = -1 ± √-55
        2 * 7 
x = -1 ± √-55         x' = -1 + √-55 = -1 + √-55 
          14                        14              14
         
                            x" = -1 - √-55 = -1 - √-55
                                      14              14
 Espero que tenho ajudado 
 
1 5 1